Jurisdiction and applicable law to non — contractual obligations arising out of restriction of competition. A case of the pharmaceutical sector - Wałachowska, Monika (Problemy Prawa Prywatnego Międzynarodowego, 2018)
In this Article the Author has analysed the most important issues arising from the interaction between intellectual property law, competition law and the right to redress, taking into account the cross-border character of the discussed matters. The cases of restraints of competition, having frequently a multinational character raise doubts as to both jurisdiction and applicable law. I believe that the EU’s legal act in this area are not well agreed. Perhaps after introducing the Directive no. 2014/104 the provisions of both Brussels I-bis and Rome II should be reconsidered, taking into account the specific character of delicts in the field of competition law. On one hand the wording of art. 6(3) of Rome II somewhat reconciles the interests of both EU-cases and non-EU cases, but the risk of applying the mosaic principle in the discussed cases seems inevitable. Perhaps for these matters the choice of law should be considered. For example the parties could have the possibility to choose the law of one of the affected markets (both of an EU-country or non-EU country, since art. 3 Rome II provides for an universal character of the regulation). When in comes to jurisdiction it is left to the courts to interpret the notion of both place of act and place of its consequences, which seems to be a propersolution. In this way we can apply a case-by-case method.